5 - Deprivation, HIV and AIDS in Northern Uganda - Peter Rwagara Atekyereza, (African Sociological Review, 2015)
This study focuses on HIV infection within the context of poverty and deprivation. The study used both quantitative and qualitative methods from a stratified random sample of 98 respondents, Key Informant Interviews and six Focus Group discussions, to investigate risk of HIV infection in Paimol Internally Displaced People’s camp in Pader district, Uganda between 2008 and 2009. This district in Northern Uganda was characterised by war and insecurity physical aggression, deprivation, hunger and family separation, among others, for over twenty years. The Study shows that in spite of the relatively high levels of HIV/AIDS awareness, some people are at risk to HIV infection as a result of these. Significantly, with resettlement after the war, most people are still deprived of basic source of livelihood, which still continues as a factor in the spread of HIV infection.